2011
DOI: 10.1007/s00590-011-0780-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there any purpose in classifying subtrochanteric fractures? The reproducibility of four classification systems

Abstract: The classification systems analysed in this study have poor reproducibility and seem to be of little value in predicting the outcome of intramedullary nailing as all of the fractures achieved union. The MCG system may be of some use in alerting the surgeon to potential problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Studies have already suggested poor reproducibility of the Seinsheimer, AO/OTA and Russell-Taylor classification systems used for subtrochanteric femur fractures and they seem to be of little value in predicting the outcome of intramedullary nailing. 17 The majority of fractures (80%) in our study were classified according to the AO classification as 32C3 with various fragment configurations ranging from three intermediate fragments to fractures with extensive shattering.…”
Section: Nowotarski and Brumbackmentioning
confidence: 97%
“…Studies have already suggested poor reproducibility of the Seinsheimer, AO/OTA and Russell-Taylor classification systems used for subtrochanteric femur fractures and they seem to be of little value in predicting the outcome of intramedullary nailing. 17 The majority of fractures (80%) in our study were classified according to the AO classification as 32C3 with various fragment configurations ranging from three intermediate fragments to fractures with extensive shattering.…”
Section: Nowotarski and Brumbackmentioning
confidence: 97%
“…There are over 15 described classifications for subtrochanteric fractures. 1 , 3 , 4 , 5 The Fielding 1 classification subdivides the fractures according to their anatomical location: type 1 fractures are those at the lesser trochanter level; type 2 fractures are those located between 2.5 and 5 cm below the lesser trochanter; and type 3 fractures are those located between 5 and 7.5 cm below the lesser trochanter. Its value is only historical, due to its low reproducibility on account of ethnic variations.…”
Section: Is There An Ideal Classification System For Subtrochanteric mentioning
confidence: 99%
“…Recently, Guyver et al 5 proposed a classification called MCG. This system is subdivided into three types: type I: lesser and greater trochanter are preserved; type II: the greater trochanter is involved, but the lesser trochanter is intact; type III: the lesser trochanter is involved (most unstable).…”
Section: Is There An Ideal Classification System For Subtrochanteric mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the intraand interobserver reproducibility of the Seinsheimer, AO, and Russell-Taylor classification systems has been shown to be poor, leading some to suggest that they offer little value in predicting the outcome of subtrochanteric femur fractures. 3…”
Section: Classificationmentioning
confidence: 99%